Electrocatalytic Reduction of Carbon Dioxide to Methane on Single Transition Metal Atoms Supported on a Defective Boron Nitride Monolayer: First Principle Study. Issue 3 (10th September 2018) - Tan, Xin; Tahini, Hassan A.; Arandiyan, Hamidreza; Smith, Sean C.
Abstract: The electrochemical conversion of carbon dioxide (CO2 ) and water into useful multi‐electron transfer products, such asmethanol (CH3 OH) and methane (CH4 ), is a major challenge in facilitating a closed carbon cycle. Here, a systematic first principle study of the potential of single transition metal atoms (Sc to Zn, Mo, Rh, Ru, Pd, Ag, Pt, and Au) supported on experimentally available defective boron nitride monolayers with a boron monovacancy (TM/defective BN) to achieve highly efficient electrocatalytic CO2 reduction (ECR) to CH4 is carried out. Our computations reveal that Fe/defective BN, Co/defective BN, and Pt/defective BN nanosheets possess outstanding ECR activities with quite low (less negative) onset potentials of −0.52, −0.68, and −0.60 V, respectively. Given that Fe and Co are nonprecious metals, Fe/defective BN and Co/defective BN may provide cost‐effective electrocatalysts. The high ECR activities of these TM/defective BN catalyst systems stem from the moderate electrocatalysts' affinities for C and O, which modulate the free energies of ECR intermediates in the reaction pathways. Moreover, it is found that Fe/defective BN and Pt/defective BN show high selectivity of ECR to CH4 . This finding highlights a strategy to design highly active and selective single‐atom electrocatalysts for ECR to CH4 . Abstract : Single transition metal atoms (Fe and Pt) supported on defective boron nitride monolayers with a boron monovacancy (TM/defective BN) are proposed as highly efficient electrocatalysts for electrocatalytic CO2 reduction (ECR) to CH4 with quite low onset potentials and high selectivity. This finding highlights a strategy to design single‐atom electrocatalysts for ECR to CH4 .